2017
DOI: 10.1016/j.bbapap.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics provides insights into biological pathways altered by plant growth promoting bacteria and arbuscular mycorrhiza in sorghum grown in marginal soil

Abstract: Sorghum is an economically important crop, a model system for gene discovery and a biofuel source. Sorghum seedlings were subjected to three microbial treatments, plant growth promoting bacteria (B), arbuscular mycorrhizal (AM) fungi mix with two Glomus species (G. aggregatum and G. etunicatum), Funelliformis mosseae and Rhizophagus irregularis (My), and B and My combined (My+B). Proteomic analysis was conducted followed by integration with metabolite, plant biomass and nutrient data. Out of 366 differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…The mycorrhizal hyphae has a strong effect on the high growth of sunflower plants Mycorrhizas combined with rhizospheric microorganisms increased nutrient uptake of maize compared to control. This supports the occurrence of changes in metabolic pathways identified during the symbiotic interaction of increased growth and nutrient uptake in plants [9]`…”
supporting
confidence: 78%
“…The mycorrhizal hyphae has a strong effect on the high growth of sunflower plants Mycorrhizas combined with rhizospheric microorganisms increased nutrient uptake of maize compared to control. This supports the occurrence of changes in metabolic pathways identified during the symbiotic interaction of increased growth and nutrient uptake in plants [9]`…”
supporting
confidence: 78%
“…The successful use of Plant-Growth-Promoting Rhizobacteria (PGPR) in agriculture is correlated with reciprocal gene regulation between bacteria and plants during plant colonization. This gene regulation exerts phytobeneficial results on biomass, nutrient uptake and metabolite upregulation [1][2][3][4][5] on proteins and biological pathways [6], as well as on gene expression [7]. In the current study, the PGPR-Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 78%
“…Under these conditions, TIM, glyceraldehyde phosphate dehydrogenase, and phosphoglycerate kinase were up-regulated (Umeda et al, 1994). Triosephosphate isomerase has been largely documented in drought tolerance plants, like wheat (Caruso et al, 2009;Ge et al, 2012;Cheng et al, 2016), rice (Gorantla et al, 2007;Sharma et al, 2012), chickpea (Khanna et al, 2014), common-bean (Zadražnik et al, 2013), coffee (Menezes-Silva et al, 2017) and sorghum (Dhawi, Datta & Ramakrishna, 2017).…”
Section: Network Interaction Predictions Based On Differential Expresmentioning
confidence: 99%
“…Arbuscular mycorrhizal (AM) fungi (Funneliformis mossae) improved performance of forage sorghum, prolonged lifespan, and significantly increased growth and protection against abiotic stress conditions (Sun, Shi & Ding, 2017). Sorghum grown in marginal soils and inoculated with four species of mycorrhizal fungi (Rhizophagus aggregatus, G. etunicatum, Funelliformis mossae and Rhizophagus irregularis), improved mineral nutrition (P, S, Fe, Ca, K, Cu, Zn) and activates a set of seven proteins (Dhawi, Datta & Ramakrishna, 2016;Dhawi, Datta & Ramakrishna, 2017). Recently, Symanczik et al (2018), demonstrated that Rhizophagus arabicus, an arbuscular mycorrhizal fungus endemic of arid ecosystems transfers more efficiently nitrogen and phosphorous than R. irregularis, strain from temperate climates in sorghum plants under drought conditions.…”
Section: Introductionmentioning
confidence: 99%